2014
DOI: 10.1016/j.jcmg.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Risk Stratification of Patients With Transthyretin Amyloidosis

Abstract: Quantitative analysis of tracer retention is capable of characterizing the severity of cardiac involvement in ATTR. By multivariate analysis, troponin T remained the only independent predictor of survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 40 publications
0
32
2
2
Order By: Relevance
“…The 2 subtypes of ATTR have been postulated to act differently; however, recent analyses have shown no difference in outcomes. 7,9,11 There was no difference in the mortality rate between genetically positive and negative patients in our study.…”
Section: Study Limitationscontrasting
confidence: 56%
See 1 more Smart Citation
“…The 2 subtypes of ATTR have been postulated to act differently; however, recent analyses have shown no difference in outcomes. 7,9,11 There was no difference in the mortality rate between genetically positive and negative patients in our study.…”
Section: Study Limitationscontrasting
confidence: 56%
“…Prior studies used less stringent inclusion criteria, including patients with interventricular septal thickness >12 mm with- out a history of severe hypertension or valvular heart disease. 4,[7][8][9]11 This may have led to an overinclusion of lower-risk patients thought to have amyloid cardiomyopathy. In this era of advanced multimodality imaging sensitive and specific for the diagnosis of cardiac amyloidosis, we feel that these modalities should be the minimum diagnostic standard of care in both clinical practice and research investigation.…”
Section: Differences Between Amyloid Subtypesmentioning
confidence: 99%
“…Planar imaging alone or with single-photon emission computed tomography (SPECT) using nonamyloid-specific, bone-avid radiotracers ( 99m Tc-DPD [3,3- [8][9][10][11][12][13][14][15][16][17] Recent data indicate that the increased level of microcalcifications may explain the enhanced affinity of bone-seeking tracers for TTR over AL amyloidosis. 18 Amyloidspecific, positron emitting 18 F-and 11 C-tagged tracers have been used successfully with positron emission tomography (PET) imaging for the identification of both AL and TTR subtypes of CA.…”
mentioning
confidence: 99%
“…Since the seminal work by Perugini et al 8 , a number of other studies have showed that 99m Tc-DPD and 99m Tc-PYP nuclear imaging is feasible and effective in detecting TTR-CA. 9,11,12,[15][16][17] In addition to the traditionally used qualitative Perugini score which compares myocardial to bone uptake and the semiquantitative HR:WBR, 8 Bokhari et al also showed that 99M Tc-PYP imaging with a heart-to-contralateral lung ratio of [1.5 detected TTR-CA with a 97% and 100% sensitivity and specificity, respectively. 16 Negative and positive example images of TTR-CA with 99M Tc-PYP imaging are depicted in Figures 1 and 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation